2009
DOI: 10.1509/jppm.28.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Choices in the United States and the Constrained Consumer: A Marketing Systems Perspective on Access and Assortment in Health Care

Abstract: One of the great American success stories of the twentieth century was the victory of medicine over disease. Its success relied on the emergence of a marketing system that delivered and managed health care. Yet, for all the success of the U.S. health care marketing system, there persists a consumption constraint of access—namely, access for whom and access to what. The purpose of this essay is to explore the effects of marketing systems on provisioning and constraining consumption and to understand the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…This article contributes to the growing research on the importance of reducing barriers (i.e., poor HIL) to health‐care access (see Mittelstaedt, Duke, and Mittelstaedt ). Results of the regression analysis demonstrate LOC, cognitive style, and financial knowledge are strongly associated with HIL, where individuals with an external LOC (H1), less analytical cognitive style (H2), and poor subjective knowledge (H3a) are generally at greatest risk of poor HIL.…”
Section: Discussionmentioning
confidence: 93%
“…This article contributes to the growing research on the importance of reducing barriers (i.e., poor HIL) to health‐care access (see Mittelstaedt, Duke, and Mittelstaedt ). Results of the regression analysis demonstrate LOC, cognitive style, and financial knowledge are strongly associated with HIL, where individuals with an external LOC (H1), less analytical cognitive style (H2), and poor subjective knowledge (H3a) are generally at greatest risk of poor HIL.…”
Section: Discussionmentioning
confidence: 93%
“…These findings reflect those of Mittelstaedt et al . () as well as Huff and Cotte (), who found that time pressure brings negative emotions to the childcare choice process. Although the accommodation model (Chaudry et al ., ) is a more advanced framework drawing from previous literature, it fails to recognise that factors like time pressure will ‘interfere’ with the process of decision‐making, which is already a product of contextual constraints and social norms.…”
Section: Resultsmentioning
confidence: 95%
“…For instance, various studies have been conducted at government-funded hospitals on social health insurance [35], health care benefits [36] or health care management education [37]. Even studies relevant to consumer buying behaviour tend to be carried out at local public hospitals rather than foreign providers and in mature economies such as US [38], UK [39] or Australia [40] or in neighbouring countries such as India and Sri Lanka. As seen above, Vietnamese research focuses mostly on the economics of social health insurance and affordability, with few considerations for non-financial factors.…”
Section: The Research Gapmentioning
confidence: 99%